A comparison of cell mediators and serum cytokines transcript expression between male and female mice infected with Mycobacterium avium subspecies paratuberculosis and/or consuming probiotics. Issue 2 (9th July 2014) - Karunasena, Enusha; McMahon, Kevin W.; Kurkure, Paresh C.; Brashears, Mindy M.
Abstract The gut immune system is complex, and dysregulation leads to a number of disorders including inflammatory bowel syndrome and (in livestock) Johne's disease. Previous work has demonstrated that males and females respond differently to treatment with pathologic and probiotic microorganisms, suggesting that a 'one‐size‐fits‐all' approach to treat GIT inflammation may be inadequate. While we had observed significant differences between males and females in terms of cytokine production, it remains unclear how these changes occur. To better understand the mechanisms, transcript expression of genes important to gut immunoregulation were monitored from male and female BALB/c mice consuming the probiotic Lactobacillus animalis (1 × 106 CFU g−1) and infected with the gut pathogen, Mycobacterium avium subspecies paratuberculosis (1 × 107 CFU). Expression of transcripts analyzed included those important to the immune system, intestinal cell differentiation, and/or regulation. Males generally displayed increased expression of Th2 and B‐cell mediators, and females showed repressed cytokine expression after MAP infection (IL‐6, TNF‐α, IL‐1 among others). Additionally, regulation of pro‐inflammatory mediators in female mice consuming probiotics suggests females responded positively to L. animalis when compared to males. Therefore, we speculate that studying mechanistic changes associated with sex and immunoregulation in gastrointestinal tissues could further elucidate host response to microorganisms.